A 21st-century shift from fossil-fuel to biogenic methane emissions indicated by 13CH4 - Schaefer, Hinrich; Fletcher, Sara E. Mikaloff; Veidt, Cordelia; Lassey, Keith R.; Brailsford, Gordon W.; Bromley, Tony M.; Dlugokencky, Edward J.; Michel, Sylvia E.; Miller, John B.; Levin, Ingeborg; Lowe, Dave C.; Martin, Ross J.; et al. (Science, 2016)
Getting a rise out of agriculture - Methane, a powerful and important greenhouse gas, has been accumulating nearly uninterruptedly in the atmosphere for the past 200 years, with the exception of a mysterious plateau between 1999 and 2006. Schaefer et al. measured methane's carbon isotopic composition in samples collected over the past 35 years in order to constrain the cause of the pause.
Gesehen am 12.05.2020